The Peace and Plenty Coverlet, the Great Chicago Fire, and a Handmade Loom: A Material Culture Exhibit of Artifacts from the Ancestors of Barbara Booth - Hein, Rachel (Kansas State University, The Chapman Center for Rural Studies, 2018)
This study covers the material culture of five selected artifacts and a brief history of the migration of Barbara Booth’s ancestors to Kansas. Each artifact has a story attached to it that gives a glimpse into the amazing history and craftsmanship in a single family, passed down through the generations. This paper uses photography, field work, interviews, research into arts and crafts, and many original primary sources from the family.
Rachel Hein, “The Peace and Plenty Coverlet, the Great Chicago Fire, and a Handmade Loom: A Material Culture Exhibit of Artifacts from the Ancestors of Barbara Booth,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/250.
Keywords: Conestoga Wagon; Council Grove; Coverlets; Jason Loomis; New England Presbyterians; Scrap blanket quilt